Pengaruh Manajemen Pengetahuan, Budaya Organisasi dan Keterlibatan Kerja Terhadap Kinerja Pegawai (The Effect of Knowledge Management, Organizational Culture and Work Involvement to Employee Performance) - Ayi Safitri; Alida Palilati; Sudirman Zaid (Pascasarjana Universitas Halu Oleo, 2021)
The objectives of the study are : (1) The effect of knowledge management, organizational culture and work involvement simultaneously have effect on Employees performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (2) the effect of partial knowledge management on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (3) The effect of partial organizational culture on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (4) The effect of partial Work involvement on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi ProvinceThe research design used was quantitative research. The population of the study were all employees who worked at the Secretariat Office of the DPRD Southeast Sulawesi Province. The analysis used is quantitative analysis using Multiple Linear Regression Analysis.The results of this study found that: (1) knowledge management, organizational culture and work involvement simultaneously have positif and signifikant effect on employee performance at the Secretariat Office of the DPRD Southeast Sulawesi Province; (2) Knowledge management has positip and significant effects on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (3) Organizational culture has has poositip and significant on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (4) Work involvement has positif and significant on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province